2017
DOI: 10.3390/atmos8080149
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Light Extinction Characteristics of Atmospheric Aerosols in Suburban Nanjing, China

Abstract: This work reports the chemical and light extinction characteristics of the atmospheric particles collected from January to November 2014 in suburban Nanjing. Size-segregated measurement results showed that more than 80% of the major aerosol components were concentrated in PM 2.5 . The concentration of PM 2.5 was highest in winter and lowest in autumn. Specifically, K + concentration peaked in late spring indicating heavy influences from straw burning, while sulfate concentration was highest in summer and its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…During the whole year ( Figure 2), the daily change trends of the concentrations of PM10 and PM2.5 in each season on the wetland and bare land were approximately similar, with the highest value at night and dusk and the lowest near noon, which was similar to the results in the Cuihu wetland [33] and Shelterbelt Site in Beijing [17]. This is probably because that the temperature is relatively lower and the humidity higher during the night and dusk which is to the disadvantage of the air flow and diffusion of PM10 and PM2.5 [35], besides, the heavy traffic event during rush hours in the early morning and at dusk is another reason [36]. whereas, PM2.5 concentration on the bare land were higher in spring and summer.…”
Section: Pm Mass Concentrationsupporting
confidence: 83%
“…During the whole year ( Figure 2), the daily change trends of the concentrations of PM10 and PM2.5 in each season on the wetland and bare land were approximately similar, with the highest value at night and dusk and the lowest near noon, which was similar to the results in the Cuihu wetland [33] and Shelterbelt Site in Beijing [17]. This is probably because that the temperature is relatively lower and the humidity higher during the night and dusk which is to the disadvantage of the air flow and diffusion of PM10 and PM2.5 [35], besides, the heavy traffic event during rush hours in the early morning and at dusk is another reason [36]. whereas, PM2.5 concentration on the bare land were higher in spring and summer.…”
Section: Pm Mass Concentrationsupporting
confidence: 83%
“…During the whole year, as shown in Figures 2 and 3, the daily change trends of the concentrations of PM 10 and PM 2.5 in each season on the wetland and bare land were approximately similar, with the highest value at night and evening while the lowest was near noon, which was similar to the results in the Cuihu wetland [34] and Shelterbelt Site in Beijing [17]. This is probably because the temperature is relatively lower, and the humidity is higher during the night and evening, which is to the disadvantage of the air flow and diffusion of PM 10 and PM 2.5 [37]; besides, the heavy traffic event during rush hours in the early morning and at evening is another reason [38]. Nguyen et al also concluded that the PM 2.5 concentration is highest in the morning [39].…”
Section: Pm Mass Concentrationsupporting
confidence: 81%
“…There was a significantly negative correlation observed between PM 10 and PM 2.5 concentrations and wind speed (p < 0.05) except in summer on the wetland; during that time, there was no significant correlation between both, as shown in Table 2. This was because wind speed in summer is the lowest (0.06 ± 0.01) among the different seasons on the wetland, and low wind speed may have a smaller effect on the diffusion of PM 10 and PM 2.5 [37]. The relatively slow wind speed favors accumulation of particles resulting in elevated pollution concentrations [17].…”
Section: Effect Of Meteorological Factors On Pm 10 and Pm 25 Concentmentioning
confidence: 99%
“…The characteristics of the fog droplet size spectrum from this observation station were compared with those from the observation stations in other areas of China, also shown in Figure 1. Specifically, these stations comprised: NJBJ (32 • 12 N, 118 • 42 E) in the northern suburbs of Nanjing [27,28]; GDZJ (21 • 1 N, 110 • 32 E) in Zhanjiang, Guangdong Province [29][30][31]; BJ (39 • 29 N, 115 • 58 E) in Beijing [32].…”
Section: Measurement and Data Processingmentioning
confidence: 99%